1998
DOI: 10.1073/pnas.95.5.2541
|View full text |Cite
|
Sign up to set email alerts
|

Synchronicity of frequently sampled, 24-h concentrations of circulating leptin, luteinizing hormone, and estradiol in healthy women

Abstract: Leptin, an adipocyte hormone, is a trophic factor for the reproductive system; however, it is still unknown whether there is a dynamic relation between fluctuations in circulating leptin and hypothalamic-pituitary-ovarian (HPO) axis hormones. To test the hypothesis that fluctuations in plasma leptin concentrations are related to the levels of luteinizing hormone (LH) and estradiol, we sampled plasma from six healthy women every 7 min for 24 h during days 8-11 of the menstrual cycle. Cross-correlation analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
186
1
25

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 272 publications
(217 citation statements)
references
References 66 publications
5
186
1
25
Order By: Relevance
“…40,43 In addition to its possible function in the regulation of tissue metabolism, leptin has modulating effects on the hypothalamic ± pituitary ± adrenal 44 and ± gonadal functions. 45 Diurnal levels of leptin correlate inversely with ACTH and cortisol levels, and an inhibitory effect of leptin on the HPA axis has been demonstrated both in mice 46 and men. 47 ± 49 This phenomenon might offer one explanation for the results presented in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…40,43 In addition to its possible function in the regulation of tissue metabolism, leptin has modulating effects on the hypothalamic ± pituitary ± adrenal 44 and ± gonadal functions. 45 Diurnal levels of leptin correlate inversely with ACTH and cortisol levels, and an inhibitory effect of leptin on the HPA axis has been demonstrated both in mice 46 and men. 47 ± 49 This phenomenon might offer one explanation for the results presented in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Talvez a leptina exerça uma ação indireta sobre os neurônios produtores de GnRH porque dois estudos não encontraram expressão combinada de mRNA para Ob-Rb e para GnRH nos mesmos neurônios hipotalâmicos (29,70). Com o intuito de observar as influências da leptina no eixo HHG em mulheres na pré-menopausa, nós determinamos as concentrações séricas da leptina, do LH e do estradiol em 6 voluntárias de peso normal (71). Amostras de sangue foram colhidas a cada 7 minutos por 24 horas durante o final da fase folicular em cada mulher.…”
Section: Reproduçãounclassified
“…Leptin secretion may have an Integrative physiology of human adipose tissue KN Frayn et al ultradian pattern 160,161 and show pulsatility with a periodicity of less than 1 h. 162 For such leptin pulsation, it has been suggested that growth hormone pulsation is the pacemaker, 163 but this remains to be proven. Systemic plasma NEFA and glycerol concentrations show pulsatility, 164 as does lipolysis in omental adipose tissue in dogs, arguing for coordinated action of adipose tissue throughout the body.…”
Section: Pulsatilitymentioning
confidence: 99%